2004
DOI: 10.1517/13543784.13.7.857
|View full text |Cite
|
Sign up to set email alerts
|

Strontium ranelate: a new paradigm in the treatment of osteoporosis

Abstract: In vitro, strontium ranelate increases collagen and non-collagenic protein synthesis by mature osteoblast-enriched cells. The effects of strontium ranelate on bone formation were confirmed as the drug enhanced preosteoblastic cell replication. In the isolated osteoclast, a preincubation of bone slices with strontium ranelate induced a dose-dependent inhibition of the bone resorbing activity of treated rat osteoclast. Strontium ranelate dose-dependently inhibited preosteoclast differentiation. The drug was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 10 publications
0
36
0
1
Order By: Relevance
“…Effect of SR on reducing risk of bone fractures and inducing bone formation and quality is explained by increased bone mineral density; 16 , 18 , 20 therefore, no significant difference was found in bone volume and number of megakaryocytes in a recent study performed by Rodriguez et al 14…”
Section: Discussionmentioning
confidence: 93%
“…Effect of SR on reducing risk of bone fractures and inducing bone formation and quality is explained by increased bone mineral density; 16 , 18 , 20 therefore, no significant difference was found in bone volume and number of megakaryocytes in a recent study performed by Rodriguez et al 14…”
Section: Discussionmentioning
confidence: 93%
“…For example, calcium (Ca) ions in bone can be exchanged with other divalent cations in serum, such as Sr. When strontium ranelate (SrR) was administrated to treat osteoporosis, Sr deposition was targeted in bone tissue and promoted bone formation while inhibiting local bone resorption [11,12]. Sr can promote bone formation even at low concentrations [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years clinical trials have been conducted on humans using a specific molecule, Sr ranelate, composed of an organic moiety that binds two stable Sr atoms for increasing Sr bioavailability. Low doses of Sr ranelate, when orally supplemented, were reported to increase vertebral bone calcification in osteoporotic patients 12, 14–16. Important pharmacological and clinical data have clearly demonstrated that the presence of this Sr‐based drug reduces the risk of vertebral17, 18 and nonvertebral fractures19 in postmenopausal women with good tolerability in patients.…”
Section: Introductionmentioning
confidence: 99%